1990
DOI: 10.1111/j.1365-2796.1990.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced plasminogen activator inhibitor activity in high consumers of fruits, vegetables and root vegetables

Abstract: We studied a cross-sectional sample of 260 subjects aged 30-60 years, in order to assess the relation between food intake habits and factors of the fibrinolytic system. Plasma samples of tissue plasminogen activator (tPA) antigen, and plasminogen activator inhibitor (PAI-1) activity were obtained for the assay. The dietary pattern was determined using a food frequency questionnaire, according to which the subjects were grouped as high, low or medium consumers. The subjects who were high consumers of fruit, veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…24 From a cross-sectional epidemiological study, it has been suggested that a high consumption of fruits, vegetables, and root vegetables may increase the activity of the fibrinolytic system. 28 If this can be confirmed, it could partly explain our findings. However, experimental evidence for that hypothesis is still lacking.…”
Section: Arteriosclerosis and Thrombosis Vol 13 No 4 April 1993 Tablmentioning
confidence: 67%
“…24 From a cross-sectional epidemiological study, it has been suggested that a high consumption of fruits, vegetables, and root vegetables may increase the activity of the fibrinolytic system. 28 If this can be confirmed, it could partly explain our findings. However, experimental evidence for that hypothesis is still lacking.…”
Section: Arteriosclerosis and Thrombosis Vol 13 No 4 April 1993 Tablmentioning
confidence: 67%
“…Reduced PAI levels, indicating increased ®brinolytic activity, have been associated with a high intake of total ®ber (Boman et al, 1994) and with a high intake of fruit and vegetables (Nilsson et al, 1990). Carbohydrate intake, especially starch and ®ber intake, was inversely associated with PAI-1, tPA, FVIIc and factor X in middle-aged men (Rankinen et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These results were in agreement with those of previous studies. A cross-sectional study of 260 subjects [127] reported an inverse dose-response association between fiber-rich food (fruit, vegetables and root vegetables) consumption and PAI-1 concentrations after adjusting for anthropometric and metabolic factors. Furthermore, Sundell and Ranby [128] also described an inverse relation between dietary fiber intake and PAI-1 activity in a study among 11 healthy subjects whose diets were supplemented with 10 g oat husk per day for 2 weeks.…”
Section: Dietary Fiber and Prothrombotic Statementioning
confidence: 99%